The student's experience of physics at the High Grammar School Živinice - Muratovic, Maksuda (Norma, 2023)
This paper presents the results of research that considers a relatively unstudied aspect of physics teaching, related to general student attitudes about learning physics, about physics as a science, physics as a possible profession, as well as emotional and motivational attitudes of students toward learning physics. In addition, an analysis was made of the differences in these attitudes by class, especially in cases where these differences are significantly expressed. The aim of this research is to study the students' attitudes towards physics as a science, to analyze the students' motivation for learning physics, to understand the different levels of students' emotions during the teaching process, and to investigate the students' interest in further studying physics. The research was conducted on a population of 110 students of the first and fourth grade of High Grammar School Živinice. Although a large number of students recognize the importance of physics as a discipline that develops scientific thinking and the ability to understand nature, the fact is that relatively few students want to pursue this science in the future. The results of this research can provide useful insights into improving the quality of physics teaching and increasing students' interest in further studies and employment in this field.
Keywords: high school; emotions; physics; motivation; student